2016
DOI: 10.1111/cobi.12784
|View full text |Cite
|
Sign up to set email alerts
|

Policy challenges and approaches for the conservation of mangrove forests in Southeast Asia

Abstract: Many drivers of mangrove forest loss operate over large scales and are most effectively addressed by policy interventions. However, conflicting or unclear policy objectives exist at multiple tiers of government, resulting in contradictory management decisions. To address this, we considered four approaches that are being used increasingly or could be deployed in Southeast Asia to ensure sustainable livelihoods and biodiversity conservation. First, a stronger incorporation of mangroves into marine protected are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 141 publications
(73 citation statements)
references
References 43 publications
0
58
1
1
Order By: Relevance
“…Moreover, storms in Tanintharyi are less severe than those that occur further north (most recently Cyclone Nargis) and hence, rehabilitation projects are less likely to be damaged, increasing rehabilitation success (Primavera et al ., ). If planned correctly and within a clear governance framework, ongoing political and economic reforms have the opportunity to improve mangrove management and rehabilitation by reforming complex natural resource governance arrangements and providing opportunities for novel public‐private financing and management of mangrove resources (Friess et al ., ). This will require the better protection and governance of mangrove forests, as currently less than 40 per cent of Tanintharyi's mangroves are legally protected (Connette et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, storms in Tanintharyi are less severe than those that occur further north (most recently Cyclone Nargis) and hence, rehabilitation projects are less likely to be damaged, increasing rehabilitation success (Primavera et al ., ). If planned correctly and within a clear governance framework, ongoing political and economic reforms have the opportunity to improve mangrove management and rehabilitation by reforming complex natural resource governance arrangements and providing opportunities for novel public‐private financing and management of mangrove resources (Friess et al ., ). This will require the better protection and governance of mangrove forests, as currently less than 40 per cent of Tanintharyi's mangroves are legally protected (Connette et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Mangrove loss in the early 21st century has declined from expected highs in the mid-to late 20th century (Spalding et al, 2010), with a global-scale remote sensing study showing that annual rates of mangrove deforestation averaged 0.2-0.7% between 2000 and 2012 (Hamilton & Casey, 2016). Some of this apparent reduction may be due to methodological differences between surveys and studies, though improved conservation successes can be an important factor as a number of countries have introduced conservation and sustainable forest-management laws and pursued community-based management (e.g., Chen et al, 2009;Friess et al, 2016), which may explain some of the reduction in deforestation rates.…”
Section: Mangrove Losses Due To Deforestationmentioning
confidence: 99%
“…However, a number of respondents reported that violations of these regulations are rampant, as many people are involved in illegal logging, poaching of wildlife, and using banned and destructive fishing practices such as poison and fine‐meshed nets, and catching undersized species. These situations are common in mangroves in many countries across the tropics, where economic resource objectives at the provincial level clash with broader national obligations for habitat conservation (Primavera, ; Friess et al ., ).…”
Section: Community Perceptions Of Other Anthropogenic Factor Of Changesmentioning
confidence: 97%